Impacts of Lower and Upper Secondary Vocational Education on Economic Growth - Lee, Hui Shan; Mun Har, Wai; Sin Yee, Lee (Journal of Technical Education and Training, 2020)
The recent global financial crisis has called for improvement on the intensity of economic challenges such as skill shortage to strengthen global economies. Vocational education and training (VET) is one of the education systems that is important for improving workersâ€™ and firmsâ€™ efficiency, productivity and competitiveness. In view of the contribution of VET in addressing labour market imbalances, it is crucial to understand that impacts of the VET on economic growth. Therefore, this study examines the impacts of lower and upper secondary VET on economic growth in 92 countries from year 2000 to 2016 by using panel regression model. The results indicate that upper secondary VET is significantly and positively influence economic growth but lower secondary VET does not affect economic growth. The study further examines the impacts of lower and upper secondary VET on the economic output indicator below and above median groups, respectively. It indicates that the effect of upper secondary VET on economic growth is stronger in the economic output indicator below median group compared to whole sample.  The implications from this study are that upper secondary VET does matter for economic growth and it is more important to the countries below median group. Therefore, policymakers need to emphasize on upper secondary VET to enhance the contribution of national investment in VET to improve economic growth.